Layer Protecting the Surface of Zirconium Used in Nuclear Reactors - Ashcheulov, Petr; Skoda, Radek; Skarohlid, Jan; Taylor, Andrew; Fendrych, Frantisek; Kratochvílova, Irena (Recent Patents on Nanotechnology, 2016)
Background: Zirconium alloys have very useful properties for nuclear facilities applications having low absorption cross-section of thermal electrons, high ductility, hardness and corrosion resistance. However, there is also a significant disadvantage: it reacts with water steam and during this (oxidative) reaction it releases hydrogen gas, which partly diffuses into the alloy forming zirconium hydrides. A new strategy for surface protection of zirconium alloys against undesirable oxidation in nuclear reactors by polycrystalline diamond film has been patented- Czech patent 305059: Layer protecting the surface of zirconium alloys used in nuclear reactors and PCT patent: Layer for protecting surface of zirconium alloys (Patent Number: WO2015039636-A1). The zirconium alloy surface was covered by polycrystalline diamond layer grown in plasma enhanced chemical vapor deposition apparatus with linear antenna delivery system. Substantial progress in the description and understanding of the polycrystalline diamond/ zirconium alloys interface and material properties under standard and nuclear reactors conditions (irradiation, hot steam oxidation experiments and heating-quenching cycles) was made. In addition, process technology for the deposition of protective polycrystalline diamond films onto the surface of zirconium alloys was optimized. Results: Zircaloy2 nuclear fuel pins were covered by 300 nm thick protective polycrystalline diamond layer (PCD) using plasma enhanced chemical vapor deposition apparatus with linear antenna delivery system. The polycrystalline diamond layer protects the zirconium alloy surface against undesirable oxidation and consolidates its chemical stability while preserving its functionality. PCD covered Zircaloy2 and standard Zircaloy2 pins were for 30 min. oxidized in 1100°C hot steam. Under these conditions α phase of zirconium changes to β phase (more opened for oxygen/hydrogen diffusion). PCD anticorrosion protection of Zircaloy nuclear fuel assemblies can significantly prolong lifetime of Zirconium alloy in nuclear reactors even above Zirconium phase transition temperatures. Even after ion beam irradiation (10 dpa, 3 MeV Fe2+) the diamond film still shows satisfactory structural integrity with both sp3 and sp2 carbon phases. Zircaloy2 under the carbon-based protective layer after hot steam oxidation test differed from the original Zircaloy2 material composition only very slightly, proving that the diamond coating increases the material resistance to high temperature oxidation. Conclusions: Zirconium alloys nuclear fuel pins’ surfaces were covered by compact and homogeneous polycrystalline diamond layers consisting of sp3 and sp2 carbon phases with a high crystalline diamond content and low roughness. Diamond withstands very high temperatures, has excellent thermal conductivity and low chemical reactivity, it does not degrade over time and (important for the nuclear fuel cladding) being pure carbon, it has perfect neutron cross-section properties. Moreover, polycrystalline diamond layers consisting of crystalline (sp3) and amorphous (sp2) carbon phases could have suitable thermal expansion. Zirconium alloys coated with polycrystalline diamond film are protected against undesirable changes and processes. Further, the polycrystalline diamond layer prevents the reaction between the alloy surface and water vapor. During such reaction, water molecules dissociate and initiate formation of zirconium dioxide and hydrogen, accompanied by the release of large amount of heat. Thus the protective layer prevents the formation of hydrogen and the release of reaction heat. Few relevant patents to the topic have been reviewed and cited.
Keywords: Raman spectroscopy